Barriers to nurses' therapeutic communication practices in a district hospital in Ghana - Evans Osei Appiah; Ezekiel Oti-Boadi; Mary Ani-Amponsah; Dorcas Goku Mawusi; Dorothy Baffour Awuah; Awube Menlah; Cindy Ofori-Appiah (BMC, 2023)
Abstract Background Patients accessing health care enter the hospital environment with extreme anxiety, fear and distress which impacts their interactions with nurses and other health care professionals who are expected to help allay these anxieties in order to enhance patients care satisfaction. However, evidence suggests that there is a lack of effective therapeutic nurse-patient interaction in hospitals and the clinical environment globally, especially in sub-Saharan Africa. Methods A qualitative research approach with an exploratory design was used to purposively select 30 participants who were engaged in face-face interactions. A semi-structured interview guide was used to conduct five audio-recorded FGDs with the 30 participants (6 in each group-2 males and 4 females) after which the discussions were transcribed verbatim, and content analyzed. Findings Two (2) main themes and 10 sub-themes emerged from the analysis of the data. The two themes were: Therapeutic communication practices and Barriers to therapeutic communication. Some of the factors identified by patients to impede therapeutic nurse-patient interaction include family interference, negative attitude from patients, patient condition, a discriminatory attitude of nurses, increased workload, and stress. Conclusion Communication practices identified in this study include nurses' manner of communication, use of touch, positive reassurance, and nurses' demeanor. Several obstacles affect communication practices, hence the need to implement measures to improve nurse-patient interaction.